Assessing the New Normal: Dangers Related to the Internet Use and Risks Facing Vulnerable Psychiatric Populations (International Journal of Studies in Nursing, 2019)
Background: Despite the social and cultural changes surrounding the immergence of social media and the risks related to internet use for adolescents, mental health screenings have not changed to assess the psycho-social implications of social media and internet use in general as social support Purpose: Mental health professionals who assess patient use of social media and internet will be informed of dangerous online support groups promoting negative coping behaviors and risk or occurrence of psychological, physical or sexual abuse arising from dangerous internet use. Method: The following databases were searched: Academic Search Premier, CINAHL Plus with Full Text, Health Source: Nursing/Academic Edition, MEDLINE, PsycARTICLES, PsycINFO, and SocINDEX with Full Text, using a combination of search terms self-harm, and Internet with Boolean phrase and, and limiters including publication years between 2010-2018. Conclusion: During the screening process, mental health professionals can begin to address this emergent concern by asking internet specific questions designed to inform the professional about patient risk concerning social media and internet use. It is important to continue to assess and evaluate screening methods to ensure mental health screenings are adapting to the changing technological world. Social media and internet use have changed the way humans communicate and form social connections. It is imperative mental health professionals assess the implications of dangerous social media and internet use concerning mental health.